A pediatric case of axial rotary fixation associated with severe head trauma requiring emergency craniotomy for hematoma removal. (December 2022) - Minamiyama, Toru; Kamidani, Ryo; Okada, Hideshi; Mizuno, Yosuke; Miyake, Takahito; Okamoto, Haruka; Kanda, Norihide; Nagaya, Soichiro; Ogura, Shinji
Abstract: Background: Atlantoaxial rotatory fixation (AARF) causes the atlantoaxial joint to be fixed in a rotated position, resulting in painful torticollis. We report a case of pediatric AARF associated with severe head trauma requiring emergency craniotomy and was treated with conservative treatment. Case presentation: A 10-year-old boy was struck by a van while walking across the street. Upon admission to our trauma care center, his Glasgow Coma Scale score was 11 points (E3V3M5), pupils were 4 mm bilateral regular circles, and other vital signs were stable. Plain computed tomography (CT) revealed left acute epidural hematoma, traumatic subarachnoid hemorrhage, cerebral contusion, pneumoencephalopathy, and rightward deviation of the axial vertebra. We performed an emergency craniotomy due to an enlarged hematoma on a repeat head CT scan and decreased level of consciousness. Based on imaging studies, rightward deviation of the axial vertebra was diagnosed as AARF; however, since the patient was already on ventilatory management and no physical findings were obtained, conservative treatment with cervical collar fixation was started. His condition improved, and he was extubated on day 3, released from the cervical collar on day 10, discharged from the hospital on day 17, and followed-up until day 32. Conclusions: AARF is often caused by minor trauma or inflammation in children; however, we experienced a case complicated by severe head trauma, which was treated conservatively and showed a good clinical progress. Since AARF treatment depends on the length of time from onset, early diagnosis, in trauma care, carefully assessing factors other than major trauma, will lead to improved prognosis.